Pemanfaatan Artificial Intelligence dalam Layanan Bimbingan dan Konseling di Sekolah - Fadhilatin Nashihah; Hana Rizqiani Khairunnisa (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The integration of Artificial Intelligence (AI) in Guidance and Counseling (GC) services in Indonesia has progressed rapidly, yet ethical challenges and its impact on student character remain a crucial debate. Objective: This study aims to map the typology of AI technology used, analyze the effectiveness of these intelligent instruments, and explore the ethical implications and their impact on student character. Methods: This research employed a Systematic Literature Review (SLR) method on 21 selected scientific articles from 2024-2026 indexed in Sinta, Scopus, and Web of Science. Data were qualitatively analyzed to address three primary research questions. Results: Findings indicate that backward chaining-based expert systems and LLM chatbots dominate precision GC services. AI is proven effective in reducing academic anxiety in 55% of students and improving emotional screening accuracy. However, there is a risk of character degradation, specifically a decrease in independence and academic integrity in 30% of respondents due to digital over-reliance. Conclusion: AI serves as a reliable diagnostic assistant for counselors but cannot replace the human role in empathy and moral authority. AI implementation must be conducted through a regulated Hybrid Counseling model to maintain a balance between technological efficiency and student character development.